Experimental evaluation of tuned liquid column damper and tuned mass damper in a space structure model. (August 2019) - Son, L; Bur, M; Andria, A D
Abstract: Vibrations in building structure due to external force can be minimalized by absorber installation. One technique in that regard is through the dynamic absorber. Previous reports have developed double dynamic vibration absorber namely Tuned Liquid Column Damper (TLCD) and spring-mass system. However, the conduct has been applied to reduce vibrations occurred on solely one-sided movement. This study investigated the double dynamics absorber utilization of Tuned Liquid Column Damper (TLCD) and spring-mass system that was designed to be capable of vibration reduction caused by interfering forces on two-sided structures hence the implementation can be more applicative.